Analisis Pengukuran Kinerja Berbasis Konsep Value For Money Pada Pemerintah Daerah Kabupaten Pekalongan - Versiandika Yudha Pratama; Syamsuddin; Farah Difa (Yayasan Pendidikan Penelitian Pengabdian Algero, 2022)
This study aims to determine the performance of the Pekalongan Regency Government in period 2017-2019 with value for money approach in economics, efficiency and effectiveness ratio. Based on the existing characteristics, this research included in descriptive quantitative research. The data analysis technique in this study uses the concept of value for money, namely assessing performance in terms of economics, efficiency, and effectiveness ratio based on local government financial performance each period. The results of the study stated that the performance of the Pekalongan Regency Government during the 2017-2019 period was categorized as economical because it produced a ratio of less than 100%. In terms of efficiency, the performance of the Pekalongan Regency Government for the 2017 is efficient, meanwhile in the 2018 and 2019 periods the performance has not been efficient because the ratio is above 100%. In terms of effectiveness, the performance of the Pekalongan Regency Government during the 2017-2019 period tends to be not optimal but has been quite effective with an annual ratio that is above the ratio of 90%.